Investigation of 25-hydroxy vitamin D deficiency in healthy adults aged 18-65 years in Istanbul, Türkiye: Investigation of 25-hydroxy vitamin D deficiency in healthy adults - Ulfer, Gozde (Journal of Medical Biochemistry, 2024)
Background :To determine the prevalence of 25-hydroxy vitamin D (25(OH)D) deficiency in healthy adult patients who presented to our hospital in Istanbul province and to present the difference between vitamin 25(OH)D levels by gender, age group, season, and month. Materials and Methods: The vitamin 25(OH)D levels of 9,778 adults who presented to the internal medicine checkup outpatient clinic of our hospital between January 2022 and December 2023 were analyzed retrospectively. Individuals with chronic disorders were excluded from the study. The adult patients included in the study were divided into two groups by age (18-50 and 51-65 years). Serum 25(OH)D levels were measured using the electrochemiluminescence immunoassay method. A serum 25(OH)D level was regarded as deficient if below 20 ng/mL, insufficient if 20-30 ng/mL, and sufficient if above 30 ng/mL. The 25(OH)D levels of the patients were investigated by age, gender, season, and month. Results: After measurement, vitamin D levels were deficient in 57.2% of the patients (n=5,592), insufficient in 28.2% (n=2,756), and sufficient in 14.6% (n=1,430). The mean vitamin D level of the 18-50 age group was significantly lower than that of the group 51-65 age group (p=0.001; p<0.01). The vitamin D levels did not statistically significantly differ by gender (p=0.085, p>0.05). The mean vitamin D levels were 17.99±10.88 ng/mL in winter, 18.11±12.69 ng/mL in spring, 22.08±11.58 ng/mL in summer, and 21.67±10.82 ng/mL in fall. There were statistically significant differences according to the season and month of hospital presentation (p=0.001; p<0.01). Conclusion: The prevalence of vitamin D deficiency (below 20 ng/mL) in healthy adults aged 18-65 years in Istanbul was 57.2%. This prevalence varied across seasons and months, indicating that sunlight is not being used sufficiently. Vitamin D deficiency in Istanbul presents a major problem that needs to be remedied.